2013
DOI: 10.1002/jgrc.20385
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven submesoscale subduction at the north Pacific subtropical front

Abstract: [1] Upper ocean observations from the north Pacific subtropical front during late winter demonstrate the generation of submesoscale intrusions by buoyancy loss. Prior to generation, a sharp thermohaline front was intensified by confluent flow of 1-2 Â 10 À5 s À1 . Relative vertical vorticity, , across a surface-intensified, along-front jet on the warm side of a frontal trough was 0.5 f. During the storm, buoyancy loss arose due to cooling of $650 W m À2 and down-front wind stress <0.5 N m À2 that generated a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“…New analysis of high-resolution model output by Su et al (2018) suggests that the Southern Ocean also has the smallest seasonal cycle of submesoscale activity. In contrast to in situ studies in subtropical regions, which predominantly found submesoscale activity in wintertime (e.g., Callies et al 2015;Hosegood et al 2013), we present evidence for intermittent episodes of a highly active submesoscale field during summer months in southern Drake Passage.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…New analysis of high-resolution model output by Su et al (2018) suggests that the Southern Ocean also has the smallest seasonal cycle of submesoscale activity. In contrast to in situ studies in subtropical regions, which predominantly found submesoscale activity in wintertime (e.g., Callies et al 2015;Hosegood et al 2013), we present evidence for intermittent episodes of a highly active submesoscale field during summer months in southern Drake Passage.…”
Section: Introductioncontrasting
confidence: 99%
“…2015; Buckingham et al 2016). Instances of symmetric instability have been observed in western boundary currents (D'Asaro et al 2011;Thomas et al 2016), and conditions suitable for symmetric instability have been documented in the subtropical open ocean in both the Atlantic and Pacific (Hosegood et al 2013) basins. However, these previous studies either have focused explicitly on the winter season or have found a particularly vigorous submesoscale field during the winter months.…”
Section: A Summer Submesoscale Activitymentioning
confidence: 99%
“…This was related to daytime surface flow from high to low density, with deeper return flow from low to high density, which would favor mixing during the following night. We found no evidence of a mean or intermittent penetration of salty waters into the pycnocline across the front during our surveys, possibly because we never encountered down-front wind situations (Hosegood et al, 2013). However, the two long stations near the front showed the presence of a salty layer under the fresher water to the west of the tongue, which, although separated by freshwater along that isopycnal from the surface water further east, must also originate from subduction of the high SSS in this region.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, wind-driven submesoscale subduction happens as well as submesoscale restratification by mixed layer eddies that play an important role in limiting the depth of the mixed layer and penetration of heat at the subsurface (Boccaletti et al 2007;Fox-Kemper et al 2008;Fox-Kemper and Ferrari 2008). These processes, not taken into account in our simple model and missed by the Argo array resolution, could impact the subduction/injection and the water mass transformation (Hosegood et al 2013). The intensive, highly resolved observations carried out within the Salinity Processes in the Upper Ocean Regional Study (SPURS) area during dedicated cruises in 2012/13 [SPURS, Subtropical North Atlantic Salinity Experiment (STRASSE), and Medidas en Microondas y Desarrollo de Algoritmos para la Misión SMOS (MIDAS)] could be later used to investigate such features in the North Atlantic subtropical region (Busecke et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noticing that submesoscale variability, including the upward convection and individual convective plumes (few kilometers; Haine and Marshall 1998;Marshall and Schott 1999) are not resolved both in the dataset and the simulation. Furthermore, the subduction can also be controlled by wind stress at submesoscale scale (Hosegood et al 2013). The development of submesoscale filaments leads to intrusion and transformation of water masses from the ML toward the interior ocean.…”
Section: Discussionmentioning
confidence: 99%